How usual behaviour can affect perceived drivers’ psychological state while driving - Cardamone, Angelo S.; Eboli, Laura; Forciniti, Carmen; Mazzulla, Gabriella (Transport, 2017)
Road accidents have a relevant impact in terms of economic and social costs. As a consequence, many research studies have focused on identifying the key factors affecting accident severity. Traditionally, these factors can be included in the infrastructural, human and vehicle groups. Among these, human factors have a relevant impact on accident severity, which depends on driving experience, driver’s socio-economic characteristics, and driving behaviour, but also on the driver’s psychological state while driving. In this paper we investigate on the relationships between driving behaviour usually taken by the driver and his/her perceived psychological state while driving. In order to achieve this goal we adopt an Ordered Probit (OP) model formulation calibrated on the basis of experimental data collected by a sample survey. We demonstrate that the adopted methodology accounts for the differential impacts of certain human factors on driver’s psychological state. First published online: 13 Jul 2015